PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF FORMING ARTISTIC TASTE AND AESTHETIC THINKING IN STUDENTS - Temirov Murodjon Anvarovich (Journals Park Publishing, 2025)
This article analyzes the features of students' perception of works of fine art (creative works) from a scientific point of view, as well as their aesthetic, psychological, and pedagogical aspects. In the work, when perceiving works of fine art, attention is paid to the numerous factors that are in the field of students' attention, including such elements as visual representation, color, and composition. The research findings reveal which mental and cognitive processes are realized in the process of students perceiving works of art. In addition, the article also discusses aspects of the perception of artistic works related to age, experience, and cultural context. The article presents new knowledge useful for scientific research in art education and art psychology.
Keywords: Visual arts, perception, creative works, aesthetics, psychology, pedagogy.